2022
DOI: 10.1155/2022/5483367
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Intestinal Parasites, Enteric Bacterial Infections, and Antimicrobial Susceptibility among Street Food Handlers in Jimma Town, Southwest Ethiopia

Abstract: Background. Food-borne infections are common public health problems worldwide. A street food handler with poor personal hygiene contributes to the transmission of intestinal parasites and enteric bacteria to the public via contaminated foods. In Ethiopia, health risks associated with street food are common. Previous studies in this area are scanty. Hence, the aim of this study was to determine the prevalence of intestinal parasites, enteric bacterial infections, and antimicrobial susceptibility among street fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
(70 reference statements)
4
6
2
Order By: Relevance
“…Our analysis found that mono-infection is caused mainly by bacteria (67.4%; n=194/288) with Salmonella spp., EPEC and Campylobacter. Our findings are consistent with other previously reported studies in Africa, 14,15 the USA and Canada, 16 Korea, 2,6 Malaysia, 26 and Italy. 10 Salmonella spp., Campylobacter and Norovirus have been known as common enteric pathogens detected in Africa, 14,15 the USA and Canada, 16 and Korea.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our analysis found that mono-infection is caused mainly by bacteria (67.4%; n=194/288) with Salmonella spp., EPEC and Campylobacter. Our findings are consistent with other previously reported studies in Africa, 14,15 the USA and Canada, 16 Korea, 2,6 Malaysia, 26 and Italy. 10 Salmonella spp., Campylobacter and Norovirus have been known as common enteric pathogens detected in Africa, 14,15 the USA and Canada, 16 and Korea.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are consistent with other previously reported studies in Africa, 14,15 the USA and Canada, 16 Korea, 2,6 Malaysia, 26 and Italy. 10 Salmonella spp., Campylobacter and Norovirus have been known as common enteric pathogens detected in Africa, 14,15 the USA and Canada, 16 and Korea. 2,6 Interestingly, we observed that there is an emergence of EPEC as one of the prevalent enteric pathogens.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“… 1 Food-borne pathogens are a class of pathogenic microorganisms that infect people through food or food-borne pathways. 2 Street food is a daily meal for an estimated 2.5 billion people worldwide. Consequently, foodborne illnesses resulting from pathogenic bacteria and parasites are increasingly becoming a significant health concern linked to street food.…”
Section: Introductionmentioning
confidence: 99%
“…11 Someone who doesn't wash their hands thoroughly and doesn't cut their nails can become a source of salmonella bacteria contaminants in food. 12 Based on a preliminary study in the Pasir Gombong area, Bekasi Regency, there were food traders who did not use mouth coverings, aprons and head coverings when selling during the pandemic. This can be a means of transmitting the virus both directly and through food if not paid attention to.…”
Section: Introductionmentioning
confidence: 99%